2009
DOI: 10.1177/1555412009343572
|View full text |Cite
|
Sign up to set email alerts
|

Discipline and Dragon Kill Points in the Online Power Game

Abstract: This article discusses the origins and development of the player-innovated dragon kill point (DKP) system as an example for thinking about Foucauldian conceptions of disciplinary power and the production of gamer subjectivity in the contexts of massively multiplayer online game (MMOG) power gaming. The argument considers the generalized hyperrationalism of DKP-based gaming as both an ideal digital form of panoptic control as well as a kind of ironic form of play with the limits of the possibility of control wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 16 publications
0
26
0
3
Order By: Relevance
“…The hyper-quantified, neoliberal way of approaching the game that grew within Impetus has been present in hardcore gaming circles since Vanilla WoW [4,14,29,32,39]. But this approach to the game was not as prevalent as it is today.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hyper-quantified, neoliberal way of approaching the game that grew within Impetus has been present in hardcore gaming circles since Vanilla WoW [4,14,29,32,39]. But this approach to the game was not as prevalent as it is today.…”
Section: Discussionmentioning
confidence: 99%
“…Paul and Philpott [33] documented social life in a guild where an increasing focus on the allocation of scarce resources (e.g., spots for in-game activities and rare weapons), created a competitive atmosphere that eventually led to the guild's demise. Silverman and Simon [39] examined guilds' use of incentives in raids. Rewarding players with an unofficial, nonmonetary currency, guilds tried to increase individual participation in raids, and increase individual loyalty to the guild.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…These systems are commonly referred to as DKP (Dragon Kill Points) systems (see e.g. Malone, 2009;Silverman and Simon, 2009;Chen, 2009). Active groups tend to utilize a wide array of ICTs, which assists in both the intra-group sharing and the tracking of contributions (Warmelink, 2014, pp.…”
Section: Guilds Corporations Clans As Information Organizationsmentioning
confidence: 99%
“…Dyer-Witheford and de Peuter began Games of Empire (2009) by remarking that the constitution of subjectivities at work in certain games is described as 'reassertion', 'rehearsal', and 'reinforcement'. And similarly, for Silverman and Simon (2009), the grind of the avatar levelling process exemplifies the disciplinary aspect of computer games. In Foucault's later work, on Greek and Roman Antiquity, his studies revealed a subject that was not constituted, but involved in constituting itself through well-ordered practices, leading him to proclaim that 'it is not power, but the subject, which is the general theme of my research.'…”
Section: Introductionmentioning
confidence: 99%